An exploratory study on marketing practices of small firms in Malacca / Runaiza Tumin - Tumin, Runaiza (Faculty of Business and Management, 2002)
As we can see, the growth of small firm and its importance to the nation's economies has been accompanied by a significant increase in interest in the nature of marketing practices. This project paper has mainly concentrated on the understanding of marketing practices and its implementation by small firms. Marketing practices here means focusing on pricing strategy, promotional strategy, channel distribution strategy, and niche marketing strategy. When we look into the scope of small businesses, the clear understanding on it assists the marketers to exploit the strengths and overcome the weaknesses, thus greatly strengthening the marketing strategy. Marketers in small firms could concentrate fully to ensure that the marketing strategy focuses on customer's mind, thus the marketing efforts are aimed directly to improve the company's profitability. Small firms also generally have very good personal relationships with their customers, enabling them to better understand the needs and wants of their customers. Thus they are able to respond effectively to fill that need, leading to satisfied customers and a more profitable venture. As a conclusion, marketers who plan properly for small firm ownership and have the right personal qualities for successful management will gain benefits and rewards from their effort for themselves and the firm itself.